On a Collection of Plants from Javadi Hills, North Arcot District, Madras State - Subramanyam, K.; Henry, A. N. (Indian Forester, 1967)
The Javadi Hills form an interesting range of hills in N. Arcot district,Madras State, and lie between 12Â°15’ and 12Â°40’ Nand 78Â°2’ and 79Â°10’ E. The area remained botanically unexplored so far and three exploration trips were conducted in the year 1958, and a total number of 296 species representing 220 genera and 76 families were collected. The vegetation at the foot and lower slopes of the hills is of the dry deciduous but type mixed with dry, semi-desert type; the fornests here are rich in Sandalwood and bamboos.Moreover, in cleared areas of these forests and in open fields and waste lands in and around small villages, many herbaceous species typical of the cold season occur; most of these disappear by the beginning of the hot season. The moist deciduous forests occur at higher elevations, particularly in the Kumbukudi, Thakarakuppam and Melpet regions; the vegetation here is dense.